Figure-Ground Mapping: Studi Tipologi-Morfologi Ruang Terbangun Kota Balikpapan - Jordan, Nadia Almira; Sherlia; Dewi, Tiara Rukmaya (LPPM ITK, 2023)
Balikpapan City, which develops heterogeneously, has an industrial area and settlement around it as the oldest area of the city. A study of the typology and morphology of the heritage zone of Balikpapan was completed to discover the city's spatial characteristics which grew multicultural and formed its built environment. Not only does the form found shows the definite shape of the urban spatial arrangement but also indicates an urban identity that can be developed sustainably. This study was conducted to determine the typology and morphology of the built area during the early development period of Balikpapan City. Through a typological-morphological analysis with a desktop survey, supported by the figure-ground maps and comparison with the theory of spatial types of urban space. The results showed that there are 4 types of typologies, which illustrate different patterns. The morphological characteristics of each typology are related to its function and generally describe the occupants. In addition, the typology indirectly shows the relationship between the form and the initial process of area formation, both planned and unplanned.